Inclusion of Metabriggsia into Hemiboea (Gesneriaceae) - Weber, A.; Wei, Y. G.; Sontag, S.; Moller, M. (Phytotaxa, 2011)
Based on molecular data and morphology, Metabriggsia is reduced to synonymy with Hemiboea and its two species transferred to that genus.